Autonomic and central nervous system correlates of cognitive control training for attentional disorders - Waitt, Alice Emily (2022)
Deficits in cognitive control and attentional processing are commonly observed in people with Attention-Deficit/Hyperactivity Disorder (ADHD) and Specific Learning Difficulties (SpLDs) such as Dyslexia. Poorer performance in the pro/antisaccade task have been observed in these individuals, which suggests impaired visual attention and inhibitory control mechanisms. Atypical cognitive processing is also related to a state of autonomic hypoarousal in conditions such as ADHD. In this thesis, I examined whether the computer-based gaze-control RECOGNeyes training program using the pro/antisaccade task could improve cognitive control of visual attention by targeting the visual attention network and whether such improvements correlate with increased arousal. A group of 35 volunteers with SpLDs and/or ADHD completed the pro/antisaccade task before and after two weeks of training their visual attention using RECOGNeyes. Magnetoencephalography (MEG), pupillometry and electrocardiography were recorded, while they performed the pro/antisaccade task. Our task performance measures, reaction time (RT) and accuracy, and reading indices improved after RECOGNeyes training. Our findings demonstrate for the first time that autonomic measures of sympathetic pupil dilation and parasympathetic cardiac deceleration both correlate with faster saccadic RTs together (which was stronger for antisaccade trials than prosaccade trials) and account for separate variance in RT. Additionally, distinct MEG oscillatory profiles were uncovered in different frequency bands within regions of the visual attention network during the pro/antisaccade task. Slow-wave oscillations of delta and theta bands show anteriorising effects, suggested to mediate timing responses and bottom-up communication from the posterior to anterior network regions. Alpha-oscillations are proposed to have top-down preparatory inhibitory effects, particularly from the bilateral frontal eye field, and alpha-suppression in the right parietal eye field. Beta amplitude presents an additional “anticipatory” event-related desynchronisation (ERD) prior to target onset that is stronger on day 2 and antisaccade trials, which could relate to generalised inhibitory control mechanisms. This thesis supports the existence of complex central and autonomic processes underlying attention and arousal that are not yet fully understood and warrant further investigation. By increasing our understanding of the integrated attentional processes and inhibitory control, this could help the development of targeted treatment solutions, such as RECOGNeyes, for ADHD and SpLDs, to improve outcomes in these individuals.